Tinea faciei on the right eyebrow caused by Trichophyton interdigitale - Kai Wen Zhuang; Ya Ling Dai; Yu Ping Ran; Jebina Lama; Yi Ming Fan (Sociedade Brasileira de Dermatologia, 2016)
Abstract Tinea faciei is a relatively uncommon dermatophyte infection entailing atypical clinical symptoms, usually misdiagnosed and treated with corticosteroids. The authors describe a case of tinea faciei on the right eyebrow caused by Trichophyton interdigitale. The patient was an 18-year-old girl, who had an inflammatory plaque with a scaly, pustular surface on the right eyebrow and upper eyelid, which had persisted for over 1 month. She was once misdiagnosed as having eczema and was treated using corticosteroid cream. A diagnosis of tinea faciei was made based on direct microscopy and culture. The sequencing of the nuclear ribosomal ITS region and β-tubulin gene of the isolate established its T. interdigitale lineage. The patient was cured by treatment with systemic terbinafine in combination with topical application of 1% naftifine-0.25% ketaconazole cream for 2 weeks.